Motion picture and video lighting for cinematographers, gaffers and lighting technicians - Brown, Blain (Routledge, 2019)
Lighting is at the heart of filmmaking. The image, the mood, and the visual impact of a film are, to a great extent, determined by the skill and sensitivity of the director of photography in using lighting. Motion Picture and Video Lighting explores technical, aesthetic, and practical aspects of lighting for film and video. It covers not only how to light, but also why. This revised edition of Motion Picture and Video Lighting is the indispensable guide to film and video lighting. Written by an experienced professional, this comprehensive book explores light and color theory, equipment, and techniques to make every scene look its best, and is heavily illustrated throughout. Three new chapters discuss best practices of using light to benefit your film, and an extensive appendix includes discussion on additional tips and tricks. In addition, a robust companion website includes up-to-date video tutorials and other resources for students and professionals alike.- Resumé vydavatel
Includes index.
Keywords: kinematografie; filmy; videofilmy; osvětlení; světelná technika; filmová technika; cinematography; films; video films; lighting; lighting technology; film equipment; elektronické knihy; příručky; electronic books; handbooks and manuals